The impact of divergent forms of social support on health-related quality of life in patients with multiple myeloma and its precursor states - Greinacher, Anja; Kühl, Rea; Mai, Elias K.; Goldschmidt, Hartmut; Wiskemann, Joachim; Fleischer, Anna; Rasche, Leo; Dapunt, Ulrike A.; Maatouk, Imad (Journal of cancer research and clinical oncology, 2024)
Multiple myeloma is a largely incurable disease. Patients suffer from the cancer, therapeutic side effects, and often psychological symptoms. Not only multiple myeloma patients but also patients with precursor diseases show high psychological distress. Today, treatment option evaluations are increasingly performed in combination with health-related quality of life (HRQoL) assessments. One factor that is positively associated with HRQoL is social support.